Nurses’ Knowledge Regarding Glasgow Coma Scale at Tertiary Care Hospital Karachi, Pakistan : Nurses’ Knowledge Regarding Glasgow Coma Scale - Bibi, Afsha; Zeeshan, Muhammad; Abbas, Ali; Awais Khan, Muhammad; Javed, Mudasar; Mahmood, Saqib; Ali khan, Mahboob; Shaikh, Muhammad Hasnain; Ali, Rizwan; Khan, Nasar (Pakistan Journal of Health Sciences, 2023)
The "Glasgow Coma Scale" (GCS) is a neurological scale used to assess the level of consciousness in patients with brain injuries. GCS measures three aspects of a patient’s neurological function: eye-opening, verbal response, and motor response. Each category is assigned a score from 1 to 4 or 1 to 5, depending on the response observed, with a total possible score of 15. Objective: To assess the nurses’ knowledge regarding Glasgow Coma Scale at tertiary care hospital in Karachi, Pakistan. Methods: This Quantitative, descriptive Cross-Sectional study was conducted at the tertiary care Hospital of Karachi, Pakistan, from September to December 2022. A total of 50 nurses were recruited through purposive sampling from the hospital’s different departments, emergency departments, Neurology, and ICUs. Moreover, those nurses who had three months of experience were included in the study. The data were collected through a valid and reliable tool that was self-administered. Results: This study’s findings revealed that Male participants were 64% and females 36%. Furthermore, findings show that 06% of participants had a low level of knowledge,72% had a moderate level of knowledge, and 22% had a high level of knowledge regarding GCS. Conclusions: Overall, these findings highlight the importance of continued education and training on GCS for healthcare professionals and the general public to ensure better outcomes for individuals who experience traumatic brain injuries.